2018
DOI: 10.1016/j.cmi.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Primary antibiotic resistance of Helicobacter pylori in Chinese patients: a multiregion prospective 7-year study

Abstract: The resistance rates to metronidazole, CLA and LEV were high in China. Patient age, gender, disease and location were associated with the resistance of H. pylori to some antibiotics. Furazolidone, AMO and tetracycline are better choices for H. pylori treatment in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
84
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 8 publications
5
84
1
Order By: Relevance
“…H pylori resistance rates to some antibiotics are increasing but may have certain regional differences. Currently, the primary resistance rate to clarithromycin is 20%‐50%, to metronidazole is 40%‐70%, and to levofloxacin is 20%‐50%, while to amoxicillin (0%‐5%), tetracycline (0%‐5%), and furazolidone (0%‐1%) remain low in China . The clarithromycin‐containing triple regimen was recommended as a first‐line treatment therapy because of its high efficacy, reduced in taking of drugs, and marginal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…H pylori resistance rates to some antibiotics are increasing but may have certain regional differences. Currently, the primary resistance rate to clarithromycin is 20%‐50%, to metronidazole is 40%‐70%, and to levofloxacin is 20%‐50%, while to amoxicillin (0%‐5%), tetracycline (0%‐5%), and furazolidone (0%‐1%) remain low in China . The clarithromycin‐containing triple regimen was recommended as a first‐line treatment therapy because of its high efficacy, reduced in taking of drugs, and marginal side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In China, clarithromycin resistance was increased rapidly, and now, the prevalence was 20%-40%. 31 Many researches showed that clarithromycin-resistant strains could affect the efficacy of tripletherapy regimen badly. 25,32 However, in quadruple therapy, it seems controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical applicability of RADB may be questionable due to the absence of a preliminary susceptibility test. Although the resistance rates of H. pylori to amoxicillin (0.1%‐4.4%), tetracycline (1.9%‐7.3%), and doxycycline (9.2%) were low in China, leading to a low probability of a strain resistant to amoxicillin or doxycycline in the included patients, data about antibiotic resistance could add further confidence. Unfortunately, due to cost‐effectiveness and patient intentions, the test for antibiotic susceptibility was absent in our study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,5 The resistance rates of H. pylori to clarithromycin (21.5%-52.6%), metronidazole (63.4%-95.4%), and levofloxacin (19.2%-54.8%) are high, while the resistance rates to amoxicillin (0.1%-4.4%) and tetracycline (1.9%-7.3%) remain low in China. [7][8][9] This indicates that the combination of amoxicillin and tetracycline might be an ideal selection. In clinical practice, the efficacy of H. pylori eradication regimens containing amoxicillin and tetracycline may not be inferior to other regimens, 10 but the general unavailability and complicated administration procedure of tetracycline have restricted its clinical application.…”
mentioning
confidence: 99%